STATE REGULATION OF RELATIONS IN THE FIELD OF CIRCULATION OF MEDICINES INTENDED FOR THE TREATMENT OF RARE DISEASES IN THE REPUBLIC OF KAZAKHSTAN - Bukatov Eric Berikovich; Gimranova G.I.; Auyezova Karlygash Tanatarovna; Khassenova Kenzhegul Kalmuratovna (Academic Journal of Physical and Chemical Sciences, 2020)
The article deals with the problems of state regulation of relations in the sphere of orphan medicines circulation in the Republic of Kazakhstan. Definitions of the terms «orphan drugs» and «rare (orphan) diseases» are given. The analysis of foreign experience of state stimulation of orphan drug manufacturers is carried out. The reasons for the lack of incentive mechanisms for orphan drug manufacturers in the Republic of Kazakhstan are considered. The legislative base in the field of orphan drugs and rare diseases list is analyzed. The procedures of expertise and registration of orphan drugs are considered. Proposals are made to improve the regulation of relations in the sphere of orphan medicines circulation. For example, the establishment of a rare diseases laboratory in Kazakhstan and the creation of continuity between the child and adult orphan drug distribution system. As a result of the study, a number of conclusions have been made that can contribute to the implementation of the policy in the field of state regulation of relations in the sphere of orphan drugs.